PRODUKTIVITAS PERIKANAN TANGKAP DI DESA SEPATIN, KUTAI KARTANEGARA - Erwansa, Erwansa (Agriculture Faculty, University of Kutai Kartanegara, Indonesia, 2019)
Sepatin village of capture fisheries productivity has increased and decreased. This research aims to determine the productivity of fishers who use the traditional fishing gear. This research uses descriptive methods and sampling used by the purposive sampling method. The results showed that fishers catch fish if in good weather conditions. Their catch is on average shrimp, fish, crab, and small crab. The fishing zone is still around the Sepatin village archipelago 2 miles from the coast